2020
DOI: 10.33578/jpfkip.v9i5.7987
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Development Orientation for Primary School in the Perspective Miller and Seller

Abstract: This research aims to describe the theoretical perspective of Miller and Seller on curriculum development at primary schools. The literature study method was applied to collect the data from relevant resources. This research finds that Miller and Keller's curriculum orientation involves transmission, transaction, and transformation. The curriculum development for primary schools in the transmission orientation emphasizes the transfer of knowledge, skills, and values to students through learning subjects. Its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Pengembangan kurikulum memberikan arah pada rencana program pendidikan dalam mencapai tujuan instruktif. Kurikulum merupakan instrumen yang menarik untuk mencapai tujuan instruktif karena program pendidikan berisi tujuan instruktif, bahan, teknik atau strategi dan penilaian (Daga, 2020). Pengembangan kurikulum pada dasarnya adalah mengkoordinasikan program pendidikan yang ada melalui berbagai pendekatan.…”
Section: Pengembangan Kurikulum Paiunclassified
“…Pengembangan kurikulum memberikan arah pada rencana program pendidikan dalam mencapai tujuan instruktif. Kurikulum merupakan instrumen yang menarik untuk mencapai tujuan instruktif karena program pendidikan berisi tujuan instruktif, bahan, teknik atau strategi dan penilaian (Daga, 2020). Pengembangan kurikulum pada dasarnya adalah mengkoordinasikan program pendidikan yang ada melalui berbagai pendekatan.…”
Section: Pengembangan Kurikulum Paiunclassified
“…Through observations and interviews conducted with teachers at Aneuk Naggroe Lhokseumawe special school, it was revealed that the current education provided in terms of faith, Sharia, and ethical issues is not entirely effective due to insufficient time allocated for islamic religious education instruction. Moreover, teachers often encounter obstacles such as students being reluctant to actively participate during question-and-answer sessions, lacking the confidence to express their thoughts and feelings openly (Daga, 2020;Ekaningrum et al, 2018). Building upon these findings, this study aims to examine in-depth the learning process employed by teachers in Islamic Religious Education at SLB Negeri Aneuk Naggroe Lhokseumawe.…”
Section: Introductionmentioning
confidence: 99%